Paulo Freire and cultural studies: clues for possible convergences (Práxis Educativa, 2021)
The aim of this paper was to analyze possible convergences between Paulo Freire’s thinking and Cultural Studies. In order to do that, Freire and Hall’s works were investigated, considering their conception of history, the presence of Marx, the centrality of culture, the importance of language, and the impact of feminist and race studies. It has been argued that both built theoretical fields averse to reductionisms and proposed an articulation between class, race and gender as a way to turn theory/policy into a means to make a difference, from the perspective of struggling against all kinds of oppression. The conclusion is that there are possible convergences between Paulo Freire and the Cultural Studies, and they may be a promising alternative for the construction of the viable unprecedented, which he always defended.Keywords: Paulo Freire. Stuart Hall. Cultural Studies.